Emergency Circumstances Theory among Shiites - Daradkh, Ayman Alian Ahmed (Journal of Islamic Sciences, 2021)
The existence of "Emergency Circumstances Theory in Islamic Jurisprudence" is considered as one of the principles that indicate the greatness of this religion and its mercy to humankind. This theory has recently appeared in the civil law. Although that, not all doctrines jurists have adopted it, they are still differing in it. Therefore, in my study, I have chosen to highlight the way that Shi’a jurists apply this theory in their doctrine. Consequently, this research aims to show the link between the pandemics’ jurisprudence and Emergency Circumstances Theory in Shia jurisprudence through declaration of theory’s truth, reviewing its conditions, examining the validity of making pandemics as the basis for Emergency Circumstances Theory. Finally, the research has concluded that there is a commonality between pandemics and Emergency Circumstances Theory; in addition, this theory has existed among Shiites.